2020
DOI: 10.1029/2020ja028492
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Mechanisms Associated With High‐Energy Electron Flux Dropout in the Earth's Outer Radiation Belt Under the Influence of a Coronal Mass Ejection Sheath Region

Abstract: Electron fluxes in the outer radiation belt are essentially governed by the dynamics of trapped particle motion in the inner magnetosphere, wherein the energetic particles execute complex periodic motions. Each motion is associated with one adiabatic invariant, namely, gyromotion around the magnetic field line, which is described as the first adiabatic invariant, bounce motion along the magnetic field line being identified as the second adiabatic invariant, and drift motion around the Earth as the third adiaba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 147 publications
(276 reference statements)
0
18
0
Order By: Relevance
“…Consequently, the interplanetary medium conditions analyzed in Figure 7 can trigger the dynamic mechanisms to deposit energy into the magnetosphere (Ponomarev et al., 2006), which can be more efficient during the solar maximum than the solar minimum. The impact of these geomagnetic storms in the inner magnetosphere is widely discussed in the literature, such as observed through the outer radiation belt's electron flux variability (Da Silva, Shi, Alves, Sibeck, Souza, et al., 2021; Murphy et al., 2018; Turner et al., 2019). The rapid electron flux decreases generally are observed during the occurrence of the strong geomagnetic storms associated with the ICMEs (Da Silva, Shi, Alves, Sibeck, Souza, et al., 2021; Turner et al., 2019), and the electron particles precipitation to the atmosphere can also occur quickly.…”
Section: Discussion and Summarymentioning
confidence: 99%
“…Consequently, the interplanetary medium conditions analyzed in Figure 7 can trigger the dynamic mechanisms to deposit energy into the magnetosphere (Ponomarev et al., 2006), which can be more efficient during the solar maximum than the solar minimum. The impact of these geomagnetic storms in the inner magnetosphere is widely discussed in the literature, such as observed through the outer radiation belt's electron flux variability (Da Silva, Shi, Alves, Sibeck, Souza, et al., 2021; Murphy et al., 2018; Turner et al., 2019). The rapid electron flux decreases generally are observed during the occurrence of the strong geomagnetic storms associated with the ICMEs (Da Silva, Shi, Alves, Sibeck, Souza, et al., 2021; Turner et al., 2019), and the electron particles precipitation to the atmosphere can also occur quickly.…”
Section: Discussion and Summarymentioning
confidence: 99%
“…This energy deposit can cause significant changes in the magnetosphere and consequently impact the ionized and neutral atmosphere. For example, the generation of magnetospheric waves in a wide range of frequencies can directly influence the energy electron flux trapped in the radiation belts (Da Silva et al., 2019, 2021), causing particle precipitation to the atmosphere. The Alfvénic fluctuations observed from May 06 to 10, 2018 (not shown here) are also important to analyze because they indicate that reconnection on the Earth's dayside magnetopause may occur.…”
Section: Resultsmentioning
confidence: 99%
“…Uncertainties are also introduced by errors in the instrument measurements and possible interpolations and fits that need to be done to acquire adequate resolution in PSD (Turner, Angelopoulos, et al., 2012). Nevertheless, careful PSD analysis is advantageous in investigating nonadiabatic outer belt electron dynamics on short timescales, for example, during the sheath and ejecta of an ICME (Da Silva et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Da Silva et al. (2020) studied an ICME sheath region that produced a small geomagnetic storm and a dropout in relativistic electron fluxes. Examining wave measurements and modeling results, they found that the dropout was likely caused by magnetopause shadowing along with ULF wave driven outward radial diffusion and local loss via pitch angle scattering by chorus and EMIC waves, which was confirmed by the PSD analysis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation